Law Enforcement Against Violations Of Privacy Rights Resulting From The Use Of Personal Data Without Consent In Electronic Media To Create Legal Awareness In Society - Yenny Febrianty; Dina Nur Maulidiah Jamil; Fauzan Azima Faturachman (UNIVERSITAS PAKUAN, 2026)
The development of information technology has increased the intensity of the use of personal data in various activities through electronic media, but on the other hand, it has also given rise to various violations of privacy rights due to the use of personal data without the owner's consent. Although Indonesia has Law Number 27 of 2022 concerning Personal Data Protection and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions, the effectiveness of law enforcement still faces various challenges. This study aims to analyze law enforcement against violations of privacy rights due to the use of personal data without consent in electronic media, based on Indonesian positive law, and to formulate an ideal concept of law enforcement to realize public legal awareness. This study uses an empirical juridical legal research method with a statutory approach, a conceptual approach, and an empirical approach. Data were obtained through literature studies and interviews with academics and law enforcement practitioners, then analyzed qualitatively using Lawrence M. Friedman's legal system theory, Soerjono Soekanto's theory of legal effectiveness and legal awareness, and Hans Kelsen's theory of legal norms. The results of the study indicate that law enforcement against violations of privacy rights has an adequate normative basis, but its implementation is not optimal due to the lack of harmonization of regulations, the limited capacity of law enforcement officers, the complexity of electronic evidence, and low public legal awareness. This study offers an ideal concept of law enforcement through strengthening legal substance, legal structure, and legal culture in an integrated manner as a law enforcement model that is not only oriented towards enforcement, but also on building public legal awareness in protecting personal data in the digital era. Keywords: Law Enforcement, Privacy Rights, Personal Data, Personal Data Protection, Legal Awareness.